Processed Red Meat and the Risks Associated with High Consumption in Brazil - Borges, Josileide Gonçalves; Negreiros, Pollyane Ferreira de; Ferraz, Jaqueline Gabrielly Alves; Soares, Ana Carolina de Lima Franco (Journal of Agricultural Studies, 2023)
Meat and its derivatives are products of high nutritional value and are widely used in people’s diets. However, red meat derivatives have a high lipid content and during storage they produce toxic compounds such as malondialdehyde. In addition, they undergo salting processes and this greatly increases sodium consumption in the final diet. The objective of this work is to analyze the content of chlorides and malonaldehydes in cured red meats and to relate it to the emergence and/or increase in the incidence of some diseases. Nineteen different types of cured red meat derivatives were analyzed for chlorides, lipids and malonaldehydes using official methodologies. The malonaldehyde (MDA) content ranged from 3.82 to 0.31 mg MDA/Kg of meat. The chloride content in the products ranged from 10.05 to 0.18 g. 100 g-1, with a meatball brand having the highest value among the tested products. The percentage of lipids ranged from 15.82 to 1.42%. The exaggerated intake of chlorides, lipids and malonaldehydes coub beemergence and/or aggravation of several diseases, therefore, it is necessary to inform the population about the reduction in the consumption of these products as a preventive measure against illness.